ENHANCING URBAN GOVERNANCE FOR INCLUSIVE GROWTH AND SUSTAINABLE DEVELOPMENT - Novita, Asti Amelia (UI Scholars Hub, 2025)
In light of global challenges such as climate change, inequality, and governance shortcomings, cities have a vital part to play in achieving sustainable development. Numerous local governance systems are deficient in transparency, public participation, and social fairness mechanisms essential for implementing sustainability. This study investigates how strengthening transparency, public engagement, and social fairness can enhance Malang City’s capacity to achieve the Sustainable Development Goals (SDGs). This study employed a mixed-methods approach, using the Sustainable Value Mapping and Analysis (SVMA) framework to assess insight from 250 stakeholders, including local officials, civil society groups, and community representatives. Findings reveal modest but statistically significant correlations among key governance indicators. For example, transparency (A1) and public participation (G3) showed a positive correlation (r=0.104), while recycling programs (D1) and gender equality in policy (G2) also correlated positively (r=0.057). Although the values are low, they point to emerging links between governance quality and SDG-aligned outcomes. The results suggest that institutional reforms in Malang are beginning to improve governance but remain limited in scope. To advance progress toward SDGs, this study recommend (1) establishing open data portals and real-time budget tracking for improved financial transparency; (2) Empowering residents financially through access to participatory funds to propose local solutions and influence budget allocations; (3) training local government staff in environmental management; and (4) integrating job training into social programs to promote inclusive growth. These actions aim to reinforce inclusive, transparent, and responsive local governance for sustainable urban development.